Knock down of NON-YELLOW COLOURING 1-like gene or chlorophyllin application enhanced chlorophyll accumulation with antioxidant roles in suppressing heat-induced leaf senescence in perennial ryegrass. (18th September 2021) - Yu, Guohui; Xie, Zheni; Chen, Wei; Xu, Bin; Huang, Bingru
Abstract : Knock down of NOL and application of the chlorophyll derivative, sodium copper chlorophyllin, result in chlorophyll accumulation and suppression of heat-induced leaf senescence. Abstract: Loss of chlorophyll and oxidative damage co-occur during heat-induced leaf senescence. This study aimed to determine the functions of a chlorophyll catabolic gene, NON-YELLOW COLOURING 1 (NYC1)-like ( NOL ), in regulating heat-induced leaf senescence and to characterize antioxidant roles of a chlorophyll derivative, sodium copper chlorophyllin (SCC), in suppressing heat-induced leaf senescence. In two separate experiments, one by comparing NOL RNAi transgenic and wild-type plants, and the other by analysing the effects of SCC treatment, perennial ryegrass ( Lolium perenne ) was exposed to heat stress (38/35 °C, day/night) or optimal temperature (25/20 °C). Results showed that both knock down of LpNOL and application of SCC suppressed heat-induced leaf senescence, as manifested by increased chlorophyll content, reduced electrolyte leakage, down-regulation of chlorophyll-catabolic genes and senescence-related genes, as well as enhanced antioxidant capacity in the peroxidase pathway for H2 O2 scavenging. Ex vivo SCC incubation protected membranes from H2 O2 damage in mesophyll protoplasts of perennial ryegrass. The suppression of leaf senescence by knocking down NOL or chlorophyllin application was associated with enhanced chlorophyll accumulation playing antioxidant roles in protecting leaves from heat-induced oxidative damage.